A functional movement screen profile of an Australian state police force: a retrospective cohort study. Issue 1 (December 2016) - Orr, Robin; Pope, Rodney; Stierli, Michael; Hinton, Ben
Abstract Background Police officers are required to perform dynamic movements in unpredictable environments, the results of which can lead to injury. Early identification of poor movement patterns of a police population, and potential sub groups within this population, may provide opportunities to treat and minimise injury risks. The aim of this study was to profile the functional movement capabilities of an Australian state police force and potential sub groups through a retrospective cohort study. Methods Retrospective data from an Australian State Police Force were provided for analysis (♂n = 1155, mean (±SD) age = 31.34 ± 8.41 years: ♀n = 357, mean age = 27.99 ± 8.02 years). Data consisted of Functional Movement Screen (FMS) assessment results of male and female trainees and qualified police officers with all assessments conducted by a qualified Police Physical Training Instructor. Results Significantly higher (U = 253863, p < .001) FMS total scores were found for recruits (mean 15.23 ± SD 2.01 points) when compared to attested officers (14.57 ± 2.96 points) and differences in FMS total scores also approached significance for females (15.24 ± 2.35 points) when compared to males (14.84 ± 2.55 points, U = 186926, p = .007), with age found to be a key, significant factor in explaining these observed differences (F (1, 1507) = 23.519, p < .001). The FMS components demonstrating poorest movement performance across all groups were the hurdle step and rotary stability. Conclusions Generally, police personnel (both attested officers and recruits of both genders) of greater age have a lower functional movement capability when compared to younger personnel, with greater percentages scoring 14 or below on the FMS. Specific conditioning programs to improve strength, range of motion and stability during identified key movement types in those demonstrating poorer movement performance may serve to reduce injuries in police personnel.